Effect of the bacterial community assembly process on the microbial remediation of petroleum hydrocarbon-contaminated soil - Zheng, Xuehao; Oba, Belay Tafa; Shen, Chenbo; Rong, Luge; Zhang, Bin; Huang, Ling; Feng, Lujie; Liu, Jiani; Du, Tiantian; Deng, Yujie (Frontiers in Microbiology, 2023)
The accumulation of petroleum hydrocarbons (PHs) in soil can reduce soil porosity, hinder plant growth, and have a serious negative impact on soil ecology. Previously, we developed PHs degrading bacteria and discovered that the interaction between microorganisms may more important in the degradation of PHs than the ability of exogenous degrading bacteria. Nevertheless, the role of microbial ecological processes in the remediation process is frequently overlooked. This study established six different surfactant enhanced microbial remediation treatments on PHs contaminated soil using a pot experiment. After 30 days, the PH removal rate was calculated; the bacterial community assembly process was also determined using the R language program; and the assembly process and the PH removal rate were correlated. The rhamnolipid enhanced Bacillus methylotrophicus remediation achieved the highest PHs removal rate and the bacterial community assembly process was impacted by deterministic factors, whereas the bacterial community assembly process in other treatments with low removal rates was affected by stochastic factors. When compared to the stochastic assembly process and the PH removal rate, the deterministic assembly process and the PH removal rate were found to have a significant positive correlation, indicating that the deterministic assembly process of bacterial communities may mediate the efficient removal of PHs. Hence, when using microorganisms to remediate contaminated soil, care should be taken to avoid soil disturbance because directional regulation of bacterial ecological functions can contribute to efficient removal of pollutants.